EFFECT OF VITAMIN C, E AND SELENIUM ON HAEMATOLOGICAL AND SERUM BIOCHEMISTRY OF ADULT MALE GUINEA PIGS - Bature, Ibrahim; Sani, Gaddafi (FUDMA Journal of Sciences, 2024)
The study was conducted to assess the biopotency of antioxidant supplements on physiological, testicular, and oxidative biomarkers in adult male guinea pigs (Cavia porcellus). A total of 60 adult male guinea pigs of three months of age with an average body weight of 500±20g were randomly allocated into three dietary treatment groups of vitamin C, E and Selenium and each comprised four varying levels with five animals per group in a completely randomized design (CRD). Feed and water was provided ad-libitum. Haematological concentration of guinea pigs in this study indicated a significant (P0.05) difference on Plasma Albumin, Globulin, Total protein, Alanine aminotranferase and Alkaline phosphate of animal supplemented with varying dosage of vitamin E and Selenium. However, a significant (P
Keywords: Guinea pigs; Haematology; Serum; Vitamins; Selenium